UHPLC-UV Method for Simultaneous Determination of Perindopril Arginine and Indapamide Hemihydrate in Combined Dosage Form: A Stability-Indicating Assay Method - Naser F. Al-Tannak (MDPI AG, 2018)
Perindopril arginine and Indapamide hemihydrate in combination were proven to have a synergistic antihypertensive impact when compared with the use of each component alone. Therefore, a new Ultra-High Performance Liquid Chromatography coupled with Ultraviolet detector (UHPLC-UV) method has been developed and subsequently validated for simultaneous determination of the anti-hypertensive combination of Perindopril arginine and Indapamide hemihydrate. The separation of Perindopril arginine and Indapamide hemihydrate was achieved using a BEH C18 (1.7 μm, 2.1 × 50 mm) analytical column (Waters® Acquity UPLC) and a mobile phase composed of 0.01% v/v formic acid in water adjusted to pH 4 with acetic acid and acetonitrile (40:60 v/v). The method was able to separate Perindopril arginine and Indapamide hemihydrate within less than 4.5 min with high accuracy, precision, resolution, and sensitivity. The content of Perindopril arginine and Indapamide hemihydrate present in the dosage form Coversyl Plus® (5000 µg of Perindopril arginine/1250 µg of Indapamide hemihydrate) was determined in triplicate to give a concentration of 4991 µg and 1247 µg, respectively, from the manufacturer's stated amounts with Relative Standard Deviation (%RSD) of ±0.63% for Perindopril arginine and ±0.84% for Indapamide hemihydrate. Moreover, the degradation products of the combination were elucidated by UHPLC-Quadrupole Time of Flight-Mass spectrometry (UHPLC-QToF-MS) under acidic, basic, and thermal conditions. In conclusion, the developed UHPLC-UV method was sensitive, rapid, and precise. Furthermore, forced degradation studies were performed and the degradants were identified by UHPLC-Electro-Spray Ionization-QToF (UHPLC-ESI-QToF).